Omori’s Law in the Occurrence of Solar Flare : Approach of Hybrid Model - Amin Najafi (Iranian Journal of Astronomy and Astrophysics)
Solar flares are large-scale phenomena that have a significant effect on theEarth’s climate. Using the solar flare time series from January 1, 2006 to July 21, 2016,we develop a complex network for predicting solar flares. In the work, hybrid modelis employed to construct complex network. In addition to the position of the flaresand their occurrence times, the energy of events based on the Telesca-lovallo modelis also used to develop solar flare network. Using constructed complex network, theOmori’s law for fore flare and after flares associated with a main flare are retrieved. Thefrequency of occurrence of solar flares decreases over time as a power law. Statisticalanalysis of flaring events catalogues indicates that a power-law dependence characterizesthe occurrence of both fore flares and after flares corresponding to a main flare. Thehybrid model reconstructs the Omori’s law for fore flare–after flare process associatedwith a main event.